Efficacy and functionality of sugarcane original vinegar on mice - Feng-Jin Zheng; Feng-Jin Zheng; Bo Lin; Bo Lin; Yu-Xia Yang; Yu-Xia Yang; Xiao-Chun Fang; Xiao-Chun Fang; Krishan K. Verma; Gan-Lin Chen; Gan-Lin Chen; Gan-Lin Chen (Frontiers in Microbiology, 2023)
IntroductionDue to their bioactive compounds and beneficial health effects, functional foods and plant-based natural medicines are widely consumed. Due to its bioactivities, vinegar is one of them that helps humans. Sugarcane original vinegar (SOV) is a special vinegar made from sugarcane as a raw material through biological fermentation processes.MethodsThe objective of this study was to assess the effects of sugarcane original vinegar on growth performance, immune response, acute oral toxicity, bacterial reverse mutation, mammalian erythrocyte micronucleus, mouse spermatogonial chromosome aberration, mammalian bone marrow cell chromosome aberration changes, and serum characteristics in mice. Distortion parameters were used to assess its safety, and at the same time, the functionality of SOV was monitored during experimentation.ResultsThe results show that the SOV has no damage or inhibitory effect on the bone marrow red blood cells of mice and no mutagenic or distortion-inducing effects on the bone marrow cell chromosomes or spermatogonia chromosomes, so it is safe to eat. SOV can improve blood lipids and reduce blood lipid content.DiscussionThe study results provide data basis for the intensive processing of sugarcane and the development of high-value SOV products. Sugarcane original vinegar has a beneficial impact on performance, immune response, and chromosomal aberration. The production application influences the vinegar's quality and, consequently, its health benefits.